Creating a better journey of care for patients with heart valve disease. Issue 3 (9th November 2021) - Sitges, Marta; Borregaard, Britt; De Paulis, Ruggero; Nolan, Paul; Woan, Wil; Pearce, Keith; Näumann, Jens; Johnson, Neil; Wait, Suzanne
Abstract: Heart valve disease has been described as 'the next cardiac epidemic', with prevalence expected to double by 2040 and triple by 2060 due to the ageing of the population. Yet until now, it has been characterized by scarce data, limited research, and low general awareness compared with other cardiovascular diseases. Effective treatment options exist for heart valve disease, and early detection and treatment can dramatically change disease progression, improve quality of life, and reduce mortality. Unfortunately, in too many patients, heart valve disease is undetected, undiagnosed, untreated, or treated too late, leading to avoidable deaths and costs, and significant compromises to people's quality of life. These gaps in the patient pathway can be remedied through appropriate policy action, with a focus on: early detection and diagnosis; timely intervention; patient-centred follow-up care; patient engagement and empowerment; psychological support; and better data to guide practice. Ensuring all patients have access to appropriate diagnosis and care without delays is imperative as we look towards rebuilding stronger and more resilient health systems, and 'build back better' after the coronavirus disease-19 pandemic. Graphical Abstract: